The Impact of Artificial Intelligence on Financial Performance: A Sample Study of Iraqi Banks - abbas azeez, hayder (Technium Business and Management, 2026)
Previous studies have not investigated directly at the influence of AI on the financial performance of the banking industry in Iraq. To address this gap, our research examines the influence of AI on the financial performance of the banking sector in Iraq. For this objective, we utilized secondary data sources from data streams and bank annual financial reports. This data covers the year 2025. In addition, we gathered data from 120 bank workers for descriptive and demographic purposes. All analyses were carried out using SPSS software. The findings revealed that AI has a positive and significant influence on banks' financial performance. Our research gives practical suggestions on how banks might employ AI to enhance their performance while requiring minimal human engagement and greatly increasing operational efficiency.